2018
DOI: 10.1242/dev.168609
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 maintains mitochondrial function during regeneration to prevent myocardial fat deposition

Abstract: Loss of the paired-like homeodomain transcription factor 2 (Pitx2) in cardiomyocytes predisposes mice to atrial fibrillation and compromises neonatal regenerative capacity. In addition, Pitx2 gain-of-function protects mature cardiomyocytes from ischemic injury and promotes heart repair. Here, we characterized the longterm myocardial phenotype following myocardial infarction (MI) in Pitx2 conditional-knockout (Pitx2 CKO) mice. We found adipose-like tissue in Pitx2 CKO hearts 60 days after MI induced surgically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Because DNMT3A has previously been described to be involved in regulating the methylome of mitochondrial DNA, 56 the observed mitochondrial impairment could in part be a direct effect of DNMT3A knockout, although further research will have to be conducted on this. It is interesting that Li et al 57 have observed lipid accumulations similar to what we saw in our EHTs in mice harboring a conditional cardiomyocyte-specific knockout of Pitx2. Although at a first glance this seems to be contradictory to the higher PITX2 expression we observed, Li et al found the fat-accumulating cells in their knockout model to be of noncardiomyocyte origin, whereas in the EHTs lipid droplets were located inside cardiomyocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Because DNMT3A has previously been described to be involved in regulating the methylome of mitochondrial DNA, 56 the observed mitochondrial impairment could in part be a direct effect of DNMT3A knockout, although further research will have to be conducted on this. It is interesting that Li et al 57 have observed lipid accumulations similar to what we saw in our EHTs in mice harboring a conditional cardiomyocyte-specific knockout of Pitx2. Although at a first glance this seems to be contradictory to the higher PITX2 expression we observed, Li et al found the fat-accumulating cells in their knockout model to be of noncardiomyocyte origin, whereas in the EHTs lipid droplets were located inside cardiomyocytes.…”
Section: Discussionsupporting
confidence: 87%
“…We found that several clusters of cells displayed unequal composition between the two genotypes. To determine which clusters were statistically different we performed a chi-square-based cluster composition test on the scRNA-seq dataset (Li et al, 2018;Xiao et al, 2018). We found that EpiCs, EndoCs, CPs, MΦs and CM-LV cells were more prevalent in Pitx2-deficient animals, whereas CM-OFT, mesenchymal cells, atrial CMs and epithelial-mesenchymal transition (EMT) cells decreased in Pitx2 mutants compared with controls ( Fig.…”
Section: Profiling Of Control and Pitx2-deficient E105 Cardiac Tissuementioning
confidence: 99%
“…The scRNA data was analyzed as previously described with minor modifications (Li et al, 2018). Briefly, raw sequencing data were handled using the 10x Genomics Cell Ranger software (www.10xgenomics.com).…”
Section: Scrna-seq and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Pitx2-induced cardiac regeneration requires physical PITX2 interaction with YAP in order to cooperatively activate ROS scavengers [65]. In addition, PITX2 has been recently reported to be required to maintain, during heart regeneration, proper mitochondrial structure and function [66]. Overall these studies highlight the importance of environmental O 2 contents and subsequently metabolism status in the regulation of cardiomyocyte proliferation and ultimately heart regeneration (Fig.…”
Section: Oxygen Exposure and Metabolismmentioning
confidence: 57%